2006
DOI: 10.1159/000094293
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Fluoride from Fluoride Dentifrices or Rinses after Use of a Calcium Pre-Rinse or Calcium Dentifrice

Abstract: The low concentration of available calcium (Ca) in oral fluids limits the formation of Ca-mediated fluoride deposits that maintain oral fluoride (F) after a topical F treatment. The purpose of this study was to examine if a high concentration of Ca would increase salivary F when used before a F rinse or dentifrice. We found that a Ca pre-rinse (150 mmol/l Ca lactate) or Ca dentifrice (0.084 g Ca glycerolphosphate per gram dentifrice) used immediately before a 60 s 228-ppm F rinse (12 mmol/l NaF) produced a 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
2
26
1
2
Order By: Relevance
“…The number of subjects (n = 12) was based on an 80% power to detect a difference of 50% with a p < 0.05. The data used in this calculation were taken from similar studies found in the literature [Vogel et al, 2006b[Vogel et al, , 2008b and previous studies performed in the laboratory [Vogel and Schumacher, 2011]. One subject withdrew from the study, and 1 subject provided too little plaque fluid for analysis so that 10 volunteers completed all parts of the study.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of subjects (n = 12) was based on an 80% power to detect a difference of 50% with a p < 0.05. The data used in this calculation were taken from similar studies found in the literature [Vogel et al, 2006b[Vogel et al, , 2008b and previous studies performed in the laboratory [Vogel and Schumacher, 2011]. One subject withdrew from the study, and 1 subject provided too little plaque fluid for analysis so that 10 volunteers completed all parts of the study.…”
Section: Subjectsmentioning
confidence: 99%
“…Such negative effects can occur both in plaque and the oral mucosa [Pessan et al, 2006;Vogel et al, 2006b;Vogel, 2011] or on enamel and within artificial enamel lesions [Barkvoll et al, 1988;Barkvoll, 1991]. SLS may also, by altering and removing structural components of the mucosa or plaque [Herlofson and Barkvoll, 1993;Robinson et al, 2006], increase the formations of fluoride deposits within these substrates as well as the rate of fluoride transport from these substrates into salivary fluid.…”
mentioning
confidence: 99%
“…The overall benefits of Ca pre-rinses on increasing oral F retention have been shown in many studies [e.g. Vogel et al, 2006], and Sr + F rinses would be expected to show a similar potential due to the similarity between Ca and Sr and the earlier reported possibility to accumulate Sr in plaque through environmental means, thus reducing the number of rinses to one and therefore increasing compliance (providing commercialization of these products). However, further research is necessary to prove these hypotheses and the suggestion that an increase in [Sr] in plaque (fluid) is directly correlated with the ability of plaque to acquire more F.…”
Section: Discussionmentioning
confidence: 95%
“…However, the inability of saliva alone to cause significant remineralization was reported in studies by Lippert et al (2004) who attributed it to the poor capacity of saliva to supply bioavailable calcium and phosphate ions to promote significant remineralization (Karlinsey et al 2008;Reynolds et al 2003;Vogel et al 2006). Furthermore, based on the nature of tooth erosion, the precipitation of substantial amounts of calcium phosphate from saliva may be frustrated by the presence of some salivary proteins (Karlinsey et al 2010a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that products with a high concentration of both calcium and fluoride may not result in greater protection because of premature reaction of these two ions during storage to form calcium fluoride. This premature reaction reduces the bioavailability of these ions, thus compromising the therapeutic efficacy of the product (Karlinsey et al 2010a, b;Vogel et al 2006). Therefore, the development of a calciumbased technology that can permit the coexistence of fluoride and calcium ions without premature reaction, offering high bioavailability of these ions to provide greater efficacy in enamel remineralization, would enhance dental health benefits with regards to dental erosion management (Amaechi and Higham 2001;Cochrane et al 2010).…”
Section: Introductionmentioning
confidence: 99%